Osteogenesis Imperfecta and Split Foot Malformation due to 7q21.2q21.3 Deletion Including COL1A2, DLX5/6 Genes: Review of the Literature - Öztürk, Özden; Bagis, Haydar; Bolu, Semih (Journal of Pediatric Genetics, 2021)
Copy number variation in loss of 7q21 is a genetic disorder characterized by split hand/foot malformation, hearing loss, developmental delay, myoclonus, dystonia, joint laxity, and psychiatric disorders. Osteogenesis imperfecta caused by whole gene deletions of COL1A2 is a very rare condition. We report a Turkish girl with ectrodactyly, joint laxity, multiple bone fractures, blue sclera, early teeth decay, mild learning disability, and depression. A copy number variant in loss of 4.8 Mb at chromosome 7 (q21.2q21.3) included the 58 genes including DLX5, DLX6, DYNC1I1, SLC25A13, SGCE, and COL1A2. They were identified by chromosomal microarray analysis. We compared the findings in our patients with those previously reported. This case report highlights the importance of using microarray to identify the genetic etiology in patients with ectrodactyly and osteogenesis imperfecta.
Keywords: 7q21 deletion; ectrodactyly; osteogenesis imperfecta; split foot malformation; SHFM